2022
DOI: 10.1097/md.0000000000030517
|View full text |Cite
|
Sign up to set email alerts
|

The systemic oral health connection: Biofilms

Abstract: Frequently, periodontal health and it's associated oral biofilm has not been addressed in those patients who have systemic health issues, especially those who are not responding to medical treatment via their physician. Oral biofilm may be present in the periodontal sulcus in the absence of clinical disease of periodontal disease (bleeding on probing, gingival inflammation) and periodontal reaction is dependent on the patient's immune response to the associated bacterial and their byproducts. Increasing eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 76 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…As pointed out, chronic gingivitis is a condition characterized by inflammation of the gums that can last for a prolonged period of time. It is caused by the buildup of plaque on the teeth, which can lead to the formation of bacterial colonies that produce toxins that irritate the gums [ 36 , 37 ]. Chronic inflammation and damage to the cells in the gums were suggested to increase the risk for oral cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out, chronic gingivitis is a condition characterized by inflammation of the gums that can last for a prolonged period of time. It is caused by the buildup of plaque on the teeth, which can lead to the formation of bacterial colonies that produce toxins that irritate the gums [ 36 , 37 ]. Chronic inflammation and damage to the cells in the gums were suggested to increase the risk for oral cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…2 Effective toothbrushing removes dental plaque 3 to prevent and reverse gingivitis, thereby reducing the risk of periodontitis, which has been associated with systemic conditions such as cardiovascular disease, diabetes, and Alzheimer's disease. 4 Therefore, for the individual, removing plaque and preventing gingivitis have the potential to improve not only oral health but also whole-body health. For society, a cost-benefit analysis 5 established that the economic burden of periodontitis is mitigated better by a strategy of prevention than of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The oral diseases caused by dysbiosis in the oral microbiota (such as periodontitis) are associated with various systemic disorders [ 11 ]. Oral bacteria and their metabolic products enter the bloodstream, increasing oral and systemic inflammation through the release of toxins or microbial by-products [ 12 , 13 ]. Much research has reported the associated risk of periodontal disease and systemic diseases such as cardiovascular disease, diabetes, respiratory infections, and adverse pregnancy outcomes, with a 19% increased risk in cardiovascular diseases and an elevated risk of gaining the critical COVID-19 infection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%